Species traits explain long‐term population trends of Finnish cuckoo wasps (Hymenoptera: Chrysididae). Issue 1 (22nd June 2017) - Paukkunen, Juho; Pöyry, Juha; Kuussaari, Mikko
Abstract: Kleptoparasitic and parasitoid insects are expected to be particularly sensitive to changes in habitat availability due to their high trophic position and small population sizes compared with their hosts, but there are only few quantitative studies on their population changes. Here, we studied the distribution and abundance of 48 kleptoparasitic and parasitoid species of cuckoo wasps (Chrysididae) and eight selected host species recorded in Finland from 1840 to 2015 based on an extensive survey of entomological collections. Population trends were assessed by studying changes in occupancy in 10 × 10 km grid squares between two study periods, 1840–1967 and 1968–2015. Statistically significant decreases in occurrence were found for 11 cuckoo wasp species and one host species, while significant increases were not observed for any species. Trends of cuckoo wasps and their hosts were positively correlated, and changes were generally stronger in cuckoo wasps than in their hosts. In a comparative analysis of species traits, abundance, body size and nesting type of host were related to occurrence changes of cuckoo wasps. Scarce and small species that use above ground‐nesting hosts declined more than abundant and large species that use ground‐nesting hosts. Cuckoo wasp species dependent on dead wood are more vulnerable to changes in the environment than species associated with open sandy habitats. While both groups of species have probably suffered from habitat loss, the emergence of secondary habitats may have benefitted species living in sandy areas and compensated for the negative impact of habitat destruction.